Multielement Ring Array Based on Minute Size PMUTs for High Acoustic Pressure and Tunable Focus Depth - Ledesma, Eyglis (Sensors (Basel), 2021)
This paper presents a multielement annular ring ultrasound transducer formed by individual high-frequency PMUTs (17.5 MHz in air and 8.7 MHz in liquid) intended for high-precision axial focalization and high-performance ultrasound imaging. The prototype has five independent multielement rings fabricated by a monolithic process over CMOS, allowing for a very compact and robust design. Crosstalk between rings is under 56 dB, which guarantees an efficient beam focusing on a range between 1.4 mm and 67 µm. The presented PMUT-on-CMOS annular array with an overall diameter down to 669 µm achieves an output pressure in liquid of 4.84 kPa/V/mm(2) at 1.5 mm away from the array when the five channels are excited together, which is the largest reported for PMUTs. Pulse-echo experiments towards high-resolution imaging are demonstrated using the central ring as a receiver. With an equivalent diameter of 149 µm, this central ring provides high receiving sensitivity, 441.6 nV/Pa, higher than that of commercial hydrophones with equivalent size. A 1D ultrasound image using two channels is demonstrated, with maximum received signals of 7 mVpp when a nonintegrated amplifier is used, demonstrating the ultrasound imaging capabilities.